Real-Time Models of Hybrid Powertrain Transmissions - Geng, Stefan; Schulte, Thomas
Hybrid electric powertrains are developed for reducing the fuel consumption and the emission of carbon dioxide. In order to support this aim, the applied control strategy can be improved by testing and developing the electronic control units by means of Hardware-in-the-Loop simulation. For the simulation, a corresponding real-time model of the powertrain is required. The development of the model is a time-consuming task due to the high dynamics and switching frequencies in the electrical subsystem, comprising the electric drives, inverter and battery and due to the various configurations of the mechanical subsystem, comprising the transmissions. In this contribution, a method for an efficient modeling of different transmission configurations for power-split systems and different types of inverter is presented. Besides the required real-time capability, the models consider the correct power flows and power losses. The presented approach is proven by means of simulation results.